Partially disordered TiO2 nanotube photonic crystal: randomness characterization and tuning of reflected scattering light. (15th October 2019) - Li, Wenshuang; Kuang, Dengfeng; Gu, Panchun; Xiang, Meng
Abstract: Introducing disorder into a periodic nanostructure can lead to specific optical behaviors. We present a method of anodic oxidation by adjusting the applied voltage and process time to introduce disorder to TiO2 nanotubes. The surface morphology of TiO2 was numerically investigated according to the morphologies measured with a scanning electron microscope by imaging processing and a statistical method. TiO2 nanotubes obtained under different fabrication conditions have various tube radii ranging from 20–40 nm and wall thicknesses ranging from 20–70 nm. We also evaluated the degree of disorder of the tube radius of the TiO2 nanotubes. The reflected scattering light distributions of laser sources were optically measured at different observing distances, which indicate that the presence of nanotubes enhances the scattering effect, reducing the scattered light intensity by more than 75%, and provide the relationship between the scattering effect and surface morphology of nanotubes. This discovery offers TiO2 nanotubes important application prospects in optical limiting and light confinement, such as stealth coating.